Swimming power test and its applications - Sokolovas, G. (FINA Golden Coaches Clinic 2016, 2016)
Dr. Genadijus Sokolovas, Senior Physiologist (Global Sports Technology) talks about "Swimming power test and its applications" at the FINA Golden Coaches Clinic 2016 (22:28 min).